2019
DOI: 10.1039/c9mt00133f
|View full text |Cite
|
Sign up to set email alerts
|

The production of reactive oxygen species enhanced with the reduction of menadione by active thioredoxin reductase

Abstract: TXNRD1 participates in the ROS production with menadione by a one-electron reduction mechanism. TXNRD1 transfers electrons from NADPH to menadione to yield a semiquinone radical intermediate, which reacts with molecular oxygen to generate ROS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Our finding was consistent with a previous study that showed TXNRD1 was a target of miR-125b-5p [83]. TXNRD1 belongs to the pyrimidine nucleotide oxidoreductases family in the thioredoxin system and is a cytoplasmic antioxidant enzyme that regulates redox homeostasis [87,88]. Overexpression of TNXRD1 is associated with highly proliferative cells and high ROS levels, such as cancer cells, contributing to protecting cells from ROS [89].…”
Section: Discussionsupporting
confidence: 92%
“…Our finding was consistent with a previous study that showed TXNRD1 was a target of miR-125b-5p [83]. TXNRD1 belongs to the pyrimidine nucleotide oxidoreductases family in the thioredoxin system and is a cytoplasmic antioxidant enzyme that regulates redox homeostasis [87,88]. Overexpression of TNXRD1 is associated with highly proliferative cells and high ROS levels, such as cancer cells, contributing to protecting cells from ROS [89].…”
Section: Discussionsupporting
confidence: 92%
“…3c ), suggesting that other mechanisms (although less efficient) may contribute to the reduction of vitamin K. Indeed, menadione can be reduced non-enzymatically by glutathione (Extended Data Fig. 5c ), and enzymatically by NQO1 and/or thioredoxin reductase in addition to FSP1 28 , 29 . Thus, genetic deletion and pharmacological inhibition of FSP1 did not significantly influence the anti-ferroptotic effect of menadione, similar to other FSP1-independent ferroptosis inhibitors (Extended Data Fig.…”
Section: Vitamin K Blocks Ferroptosis Via Fsp1mentioning
confidence: 99%
“…[ 62 ] Endogenous antioxidants such as thioredoxin reductase‐1 even exaggerate the generation of ROS via redox cycling. [ 63 ] Intracellular H 2 O 2 can be produced via incomplete mitochondrial respiration, which could lead to mitochondrial membrane depolarization, lipid peroxidation, and DNA damage and induce beta‐cell apoptosis. [ 64–66 ]…”
Section: Discussionmentioning
confidence: 99%